Survey of protozoa and metazoa populations in wastewater treatment plants by image analysis and discriminant analysis - Amaral, A. L. (2004)
The biota present in the activated sludge of a wastewater treatment plant are mainly composed of bacteria, Protozoa and Metazoa. The Protozoa and Metazoa species are important micro-organisms taking part in the ecosystem balance in wastewater treatment plants and are quite sensitive to physical, chemical and operational processes. Several authors have established relationships between the predominance of certain species or groups and some variables of the plant. Such analysis demands the identification and quantification of the different species, which requires skilled workers, specializing in zoology or protozoology, and is time-consuming. To overcome those problems, semi-automatic image analysis and discriminant analysis were carried out for the identification procedures. The overall results were very promising in terms of Protozoa and Metazoa group recognition and of survey of plant conditions. Copyright 2004 John Wiley & Sons, Ltd.